Diagnóstico de Circuitos Integrados Analógicos y de Comunicaciones (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
This paper is a brief review on the diagnostic strategies used in the design and manufacture of analog integrated circuits in general, but with emphasis on those used in communications. Explains the paradigms governing modern electronic design. In light of these paradigms, after reviewing the most important aspects of modern microelectronic design, from a qualitative perspective and a brief exploration about the types of diagnosis that can be found starting from the failure to detect. Next introduces some common strategies for the diagnosis of integrated circuits for communications, as well as some neural approaches. We discuss about the aspects that make very particular design and diagnosis of integrated circuits for communications and the comparison between the different techniques. The article proposes a strategy that combines technical neuronal MADBIST with a neural network to perform the diagnosis.